Outside front cover: Advancing translational research with next‐generation protein microarrays. Issue 8 (April 2016) - Yu, Xiaobo; Petritis, Brianne; LaBaer, Joshua
Abstract : DOI:10.1002/pmic.201500374 In the cover image, Xiaobo Yu et al. use traffic signals to echo the images of the protein arrays both to capture the notion of accelerating discovery and capture the notion that arrays are used to understand signaling . For more details, see the article by Xiaobo Yu et al. on page 1238.